The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1966
DOI: 10.1901/jeab.1966.9-619
|View full text |Cite
|
Sign up to set email alerts
|

A COMPUTER ANALYSIS OF SERIAL INTERACTIONS IN SPACED RESPONDING1

Abstract: Serial dependencies in interresponse times were studied by means of a digital computer. In monkeys exposed to a DRL 20-sec schedule of reinforcement, serial interactions appeared at all stages of training. Early in training the serial effects consisted of trains of relatively long interresponse times interspersed among trains of relatively short ones. Later on, the serial effects appeared to be characterized by a tendency to drift up and down in long wavelength periods around the minimum interval required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1971
1971
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Increasing m will decrease the effect of any first or higher order sequentials. The latter are seldom observed at substantial levels in operant behavior, even when explicitly reinforced (see Shimp, 1973;Weiss, Laties, Siegel, & Goldstein, 1966). Hence, m must be large enough to attenuate the effects of sequential dependencies but small enough to reflect the current response distribution.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing m will decrease the effect of any first or higher order sequentials. The latter are seldom observed at substantial levels in operant behavior, even when explicitly reinforced (see Shimp, 1973;Weiss, Laties, Siegel, & Goldstein, 1966). Hence, m must be large enough to attenuate the effects of sequential dependencies but small enough to reflect the current response distribution.…”
Section: Methodsmentioning
confidence: 99%
“…A time series with slow, long-wavelength fluctuations will then show most of its power at low frequencies, and a rapidly varying time series will show a preponderance of power at high frequencies. Such an analysis was undertaken by Weiss, Laties, Siegel, and Goldstein (1966), to quantify some of the serial aspects of spaced-responding performance. It demonstrated that, at least under the specific conditions of the experiment, spaced-responding performance displays long-wavelength oscillations in IRT duration.…”
Section: Spaced Respondingmentioning
confidence: 99%
“…They also make no assumptions about the statistical structure of a time series and are fairly simple to conduct. They are also fairly simple to interpret because, as Edgington (11) (14) and of interresponse times in schedule-controlled operant behavior (15).…”
mentioning
confidence: 99%